SOCIAL QUALITIES IMPOSED ON THE TEACHER'S PERSONALITY - Kochkarova Elmira Rashidovna (Web of Journals Publishing, 2024)
This article provides information on the pedagogical requirements and social qualities of a teacher.
Keywords: Pedagogy, teacher, pedagogue, science, development, education.